Analisis Strategi Pemasaran Shopee Nronlineshop_ Untuk Mengembangkan Bisnis Ke Pasar Internasional - Nadya Rahmadhani; Dilla Syadzwina; Lenti Susanna Saragih; Aurora Elise Putriku (Pusat Riset dan Inovasi Nasional, 2024)
This journal aims to analyze the marketing strategies implemented by nronlineshop_, an online shop business focusing on the sale of women's accessories and fashion, in expanding their business to the international market on the Shopee platform. With a focus on the international market, effective marketing strategies become the key to achieving success in global expansion. In an increasingly competitive and global business world, Integrated Marketing Communication (IMC) and Public Relations Marketing strategies become integral parts of the marketing strategy applied by Nronlineshop_. The objective is to enhance the visibility and competitiveness of Nronlineshop_ in the international market. In this research, the author uses a literature study approach and a qualitative approach by conducting interviews with the owner of nronlineshop_ and analyzing the marketing strategies implemented in promoting their products through Shopee. The research findings show that nronlineshop_ has successfully increased the visibility and sales of their products by implementing innovative and effective marketing strategies on the Shopee platform. The strategies include the use of Integrated Marketing Communication (IMC) methods and Public Relations Marketing, which incorporate marketing elements such as advertising, sales promotion, public relations, and integrated communication strategies. This research provides important contributions to the understanding of marketing strategies in international businesses, particularly on the Shopee platform. The implications of these findings can provide insights for other companies looking to enhance their marketing strategies on e-commerce platforms.